Tradition and Change in Contemporary West and East African Fiction. - Okuyade, Ogaga (Matatu ;, 2014)
The essays in this volume capture the exciting energy of the emergent novel in East and West Africa, drawing on different theoretical insights to offer fresh and engaging perspectives on what has been variously termed the 'new wave', 'emergent generation', and 'third generation'. Subjects addressed include the politics of identity, especially when (re)constructed outside the homeland or when African Indigenous values are eroded by globalization, transnationalism, and the exilic condition or the self undergoes fragmentation. Other essays examine once-taboo concerns, including gendered account.